Knowledge Sharing Types as Predictors of Job Performance Mediated by Problem-Solving Self-Efficacy in the Information System Integration Service Industry - Hong, Jon-Chao; Lee, Yi-Fang; Chen, Hsin-Han; Nguyen, Hoang Bao Ngoc (Frontiers in Psychology, 2022)
Drawing on social exchange theory, knowledge sharing plays a key role in enhancing the competitiveness of enterprises, in particular, in information technology (IT) enterprises, which often have to face the pressure of solving problems under time pressure. Under such pressure, employees will seek and share knowledge to find solutions. However, few studies have focused on the personal characteristics affecting the knowledge sharing of System Integration IT workers. To address this gap, the present study explored how the effectiveness of job performance can be predicted by knowledge based on a micro ecological system and knowledge sharing types. Data was collected from 307 System Integration IT workers by using snowball sampling method via a Google questionnaire. After performing confirmatory factor analysis with structural equation modeling, it was found that problem solving efficacy (PSSE) can positively predict four knowledge sharing types (i.e., automatic response, rational reflection, ridiculed reflection and stolen reflection); except for stolen reflection, the others can positively predict job performance. The implication of this study is that automatic response systems and rational reflection systems in knowledge sharing can enhance job performance, supported by PSSE. It is hoped that managers can generate System Integration workers’ rational reflection to effectively evoke knowledge sharing.